Pengaruh Relaksasi Dan Meditasi Terhadap Kecemasan Ibu Hamil Trimester III - Rachmawati Ika Sukarsih (Sinar : Jurnal Kebidanan, 2022)
Objective: To determine the effect of relaxation and meditation on the anxiety of third-trimester pregnant women.Methods: This study uses a quasy experimental design with pre-test and post-test. The sample used in this study comprised ten respondents through the total sampling technique. This research was conducted in October 2020. The research instrument used in this study used the Numerical Rating Scale (NRS) observation sheet, standard operating procedure (SOP) relaxation and standard operating procedure (SOP) meditation. The data obtained were then analysed using paired t-test and independent-test statistics to determine the effect of the two interventions on anxiety in third-trimester pregnant women.Results: Most mothers in the relaxation and meditation group were aged 26-35 years, namely seven people (70.0%) and eight people (80.00%). Based on parity, the number of primiparas and multiparas (50.00%) in the relaxation group was the same. Based on education, most mothers had secondary education in the relaxation group, namely five people (50.00%), and in the meditation group, there were eight people (80.00%). Based on occupation, most pregnant women did not work in the relaxation group, namely six people (60.00%). In the meditation group, the number was the same between working and non-working mothers (50.00%).This study showed that the mean difference in the relaxation group was 14.4142, while the mean difference in the meditation group was 34.224, t = -5.316 and p=0.000. The mean difference in the meditation group was more significant than in the relaxation group and p=0.000.Conclusion: There is a significant difference in the effect of relaxation and meditation on anxiety levels in third-trimester pregnant women. Based on the results of this analytical test, meditation is more effective than relaxation in reducing anxiety levels in third-trimester pregnant women at RSI Darus Syifa', Surabaya.